Cash Flow Management and Assets Growth of Listed Industrial Goods Firms in Nigeria - Idehen, Osatohanmwen Favour; Jackson-Akhigbe, Beauty; Abusomwan, Rachael (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study examined the effect of cash flow management on asset growth among listed industrial goods firms in Nigeria. Specifically, it evaluates how cash flow from operating, investing, and financing activities and cash flow per share contribute to asset growth. The multi-level mixed effect (MLME) regression analysis estimator was used to test the hypotheses. Adopting an ex post facto research design, this study evaluates a sample of fifteen industrial goods firms listed on the Nigerian Exchange Group, selected based on their continuous listing from 2018 to 2023 and the availability of their annual reports, where data were sourced. The descriptive and inferential statistical methods were used, with preliminary tests of normality and multicollinearity checks to guide the regression analysis. The results indicated that cash flow per share does not significantly influence asset growth, but the cash flow from operating, investing, and financing activities has positive influences on asset growth during the period under investigation. This study concludes that effectively managing investing, financing, and operating cash flow activities is essential for asset growth. Based on the findings, this study recommends that stakeholders, including investors, management, and policymakers, should prioritize strategies that enhance cash flow management. Industrial goods firms in Nigeria should focus on optimizing operational cash flow through improved revenue generation and cost management while leveraging financing opportunities to support asset growth. Additionally, prudent investment in productive assets should be given priority, which will further strengthen asset growth opportunities.
Keywords: Asset Growth; Cash Flow Management; Financing Activities; Investing Cash Flow; Operating Cash Flow